109k views
5 votes
Lars is balancing equations with his study group. He is unsure about one equation because each member of the study group came up with a different answer. Which is the proper way to balance the equation Ca(OH)2 + H3PO4 → Ca3(PO4)2 + H2O? Ca(OH)2 + H3PO4 → Ca3(PO4)2 + 6H2O 3Ca(OH)2 + 2H3PO4 → Ca3(PO4)2 + 6H2O 3Ca(OH)2 + 2H3PO4 → Ca3(PO4)2 + 3H2O Ca(OH)2 + 2H3PO4 → Ca3(PO4)2 + 6H2O

User Kbirk
by
6.0k points

2 Answers

5 votes

Answer:

b

Step-by-step explanation:

User Tia
by
4.9k points
5 votes

Answer:

3Ca(OH)2 + 2H3PO4 → Ca3(PO4)2 + 6H2O

Step-by-step explanation:

This a proper way to balance the equation:

- Count the OH from the base (2)

- Count the H from the acid (3)

We can make 2 molecules of H₂O but we still have one more H

H₃PO₄ → dissociates in → 3H⁺ + PO₄³⁻

Ca(OH)₂ → dissociates in → Ca²⁺ + 2OH⁻

So, to form the salt, you must have 3 Ca²⁺ to react with 2 (PO₄³⁻) to make global charge of +6/-6

Therefore, if you have 3 Ca in the salt, you may have 3 Ca in the base.

So, if you have 2 phosphate in the salt, you must have 2 PO₄³⁻ in the acid.

Now you have 6 protons in the acid (6H) and 6 (OH) in the base; in conclussion you can make 6 H₂O.

Finally the ballance equation is:

3 Ca(OH)₂ + 2 H₃PO₄ → Ca₃(PO₄)₂ + 6H₂O

User Adam Pearlman
by
6.1k points